O Gabinete do Ministro e Secretário de Estado dos Negócios Estrangeiros e da Guerra (1804-1808) : Análise da produção informacional - Rodrigues, Abel (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper focuses on the Count of Barca archive, also known as the “Barca-Oliveira Archive”. António de Araújo de Azevedo, Count of Barca (1754-1817), was Minister and Secretary of State for Foreign Affairs and War between 1804 and 1808. He produced, collected and accumulated immense official information which is found in his archive, lacking its original production context. In order to comprehend the emergence and establishment of information flows, we resort to an interdisciplinary study that calls upon History and Archivistic, an applied subject of the Information Science degree.